STUDI LITERATUR PERAN PENDIDIKAN KEWARGANEGARAAN (PKn) DALAM MEMBANGUN KARAKTER KESIAPSIAGAAN BENCANA PADA SISWA SEKOLAH DASAR - Bherrio Dwi Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia is a country with a high level of disaster vulnerability, making strengthening disaster preparedness through education from an early age a pressing need. This study aims to analyze the role of Civics Education (PKn) in developing disaster preparedness in elementary school students through a literature review. The method used was a literature review, examining various scientific articles, books, and relevant documents related to disaster education, disaster literacy, character education, and PKn learning. Data was collected through searches on Google Scholar, then analyzed using content analysis techniques. The results of the study indicate that disaster literacy is an important foundation in building student preparedness, while schools play a strategic role in fostering a culture of disaster awareness through curriculum integration, simulations, and the promotion of safe behaviors. Disaster education has been proven effective in improving students' knowledge, attitudes, and skills in dealing with disasters. In this context, Civics plays a unique role because it not only develops civic knowledge but also fosters the values ​​of responsibility, discipline, social awareness, solidarity, and mutual cooperation, which are highly relevant to disaster preparedness. Thus, Civics has the potential to become an integrative vehicle for developing disaster literacy-based learning for elementary school students.